THE INFLUENCE OF SERVICE QUALITY AND TRUST ON SHARIA COMPLIANCE SUSTAINABILITY - Faridy, Najihatul; Sri Nugroho, R. Dwi Widi Pratito; Susanto, Susanto; Santoso, Aprih; Awaludin, Dipa Teruna (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study focuses on the merger of three Islamic banks into Bank Syariah Indonesia (BSI), a significant development in Islamic banking in Indonesia. This merger presents a fundamental issue for examining how customers respond to and contribute to the sustainability of Sharia compliance at BSI. Using a descriptive quantitative approach, this study collected data from 252 BSI customers selected through purposive sampling. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings indicate that service quality has a positive and significant influence on the sustainability of Sharia compliance. Conversely, trust does not significantly influence the sustainability of Sharia compliance.